Tofacitinib, an Oral Janus Kinase Inhibitor: Perspectives in Dermatology - Kostovic, Kresimir; J. Gulin, Sandra; B. Mokos, Zrinka; Ceovic, Romana (Current Medicinal Chemistry, 2017)
Background: Tofacitinib (formerly known as CP-690,550, CP690550, tasocitinib), a novel selective immunosuppressant, is a small molecule classified as Janus kinase inhibitor. The aim of this review article is to present updated data summary on the tofacitinib in the field of dermatology. Method: We undertook a structured search of bibliographic databases for peer-reviewed scientific articles, including review articles, original research articles as well as case report articles based on inclusion/exclusion criteria. Technical reports on tofacitinib from U.S. Food and Drug Administration and European Medical Agency were also included. Results: Forty-three papers were included in this review. We report current data on tofacitinib chemical properties, pharmacology, non-clinical toxicity, as well as efficacy and safety in potential new indications in dermatology: psoriasis, alopecia areata, vitiligo, atopic dermatitis and nail dystrophy associated with alopecia areata. Conclusion: JAK/STAT pathway has an important role in the pathogenesis of psoriasis, alopecia areata, atopic dermatitis, and vitiligo. Despite encouraging efficacy, due to concerns about the overall safety profile of tofacitinib, additional studies will have to determine the adequate risk-to-benefit ratio.
Keywords: CP690550